2022
DOI: 10.1186/s12890-022-02133-5
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic ultrasonography-based rapid shallow breathing index for predicting weaning outcome during a pressure support ventilation spontaneous breathing trial

Abstract: Background The optimum timing to wean is crucial to avoid negative outcomes for mechanically ventilated patients. The rapid shallow breathing index (RSBI), a widely used weaning index, has limitations in predicting weaning outcomes. By replacing the tidal volume of the RSBI with diaphragmatic excursion (DE) and diaphragm thickening fraction (DTF) assessed by ultrasonography, we calculated two weaning indices, the diaphragmatic excursion rapid shallow breathing index (DE-RSBI, respiratory rate [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 45 publications
0
0
0
1
Order By: Relevance
“…In this case, there is no means to distinguish which part of displacement is passive, and which is active. Moreover, DE varies depending on the patient's position, breathing pattern and abdominal and/or thoracic pressure [34]. Consequently, DE may not be a reliable parameter for monitoring diaphragm contractile activity during PSV.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, there is no means to distinguish which part of displacement is passive, and which is active. Moreover, DE varies depending on the patient's position, breathing pattern and abdominal and/or thoracic pressure [34]. Consequently, DE may not be a reliable parameter for monitoring diaphragm contractile activity during PSV.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Fossat G found that the ratio of RSBI and RSBI/DE could not predict weaning success, but combining ultrasound DE and DTF as predictive indicators might be worth further investigation ( 17 ). The study by Song J revealed that the sensitivity of DE-RSBI is 89.2%, specificity is 56.9%, with an AUC of 0.813.While DTF-RSBI shows a sensitivity of 67.6%, specificity of 93.2%, with an AUC of 0.859 ( 18 ). Despite the limited research on the ultrasound indicators of diaphragm function, DE-RSBI and DTF-RSBI, in predicting extubation outcomes in mechanically ventilated pediatric patients, existing studies have confirmed that high DE-RSBI and DTF-RSBI are independent risk factors for extubation failure in adults ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…These parameters, and particularly the thickening fraction, have been explored as non-invasive predictors of ventilation or weaning failure in mechanically ventilated patients in the ICU setting, as discussed above [16,25,42,[45][46][47][48]. There is no established consensus yet regarding the superiority of either diaphragmatic thickening fraction or excursion as a predictor of clinical outcomes in the intensive care setting, with some studies suggesting a superiority of the former [49,50] or latter [51][52][53] technique. A systematic review published in 2021 concluded that the thickening fraction had slightly lower sensitivity but higher specificity than the diaphragmatic excursion in predicting successful weaning from mechanical ventilation [54], but the analysis was potentially hindered by the significant heterogeneity between the studies.…”
Section: Measurement Normal Rangementioning
confidence: 99%